The Ideology Critique of Mearsheimer’s Theory of Offensive Neorealism: The Case of Russia-Ukraine War and Its Ideologization in Indonesia - Musa Maliki; Dini Putri Saraswati (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
This article examines the ideology critique of Mearsheimer’s theory of offensive neorealism because his theory preoccupies the reality of world politics, especially in the Russia-Ukraine War case. In the International Relations (IR) discipline, we have problems with a methodology and its assumptions, especially mainstream theories which reduces the reality of world politics. In this regard, we view neorealism has problems. After Waltz’s theory of defensive neorealism, Mearsheimer’s theory is becoming the ideology of IR to make sense of world politics, especially in Indonesia where scholars of IR mostly quote Mearsheimer as the master who knows deeply, the Russia-Ukraine War. By using the critical theory approach, we argue that the theory of offensive neorealism is ideological because this theory is believed as a ‘faith’ to make sense of the reality of the Russia-Ukraine War without questioning the epistemological and methodological assumptions. Neorealism is still a mainstream theory in IR, especially in Indonesia. We will conduct the ideology critique of Mearsheimer’s theory in order to argue that offensive neorealism is a theory that supports great-power countries, including their ideological practice to maintain their positions. In the frame of offensive neorealism, whether you are against or pro-Ukraine, it does not matter because, in the end, this theory only represents, sees, and observes great power countries like Russia and America while the weak states should realistically accept big power countries. Therefore, the theory of offensive neorealism does not seem to consider small countries.